Eating disorder professionals' perceptions of oral health knowledge. Issue 3 (9th October 2015) - Johnson, LB; Boyd, LD; Rainchuso, L; Rothman, A; Mayer, B
Abstract: Objective: The aim of this study was to assess the oral health knowledge among professionals who specialize in treating eating disorders, and identify to what extent their education, and training addresses oral health care delivery, and recommendations for individuals with eating disorders. Method: Participants for this study were licensed behavioural and medical providers specializing in eating disorder treatment ( n = 107), and recruited through professional eating disorder organizations. Participants completed an anonymous, online questionnaire (33 items) assessing level of oral health‐related education, knowledge and treatment recommendations within the participant's respective eating disorder discipline. Results: The majority of respondents (85%) were formally trained in eating disorders, and of those trained, 64.4% were not satisfied with the level of oral health education during formal education, and 19.5% report no oral health education. Respondents consider their knowledge of risk of oral disease for their clients/patients as average or above (84%), and ranked tooth erosion as the greatest reason for oral care (63%) while dry mouth led in the rankings for least significant reason for oral care (33%). Referral for oral care was found to be more common after reports of complication (55%). Discussion: According to these findings, eating disorder professionals regard oral health care for their clients as significant, and may be unaware of associated oral risk factors, current oral care standards and long‐term oral effects of disordered eating apart from enamel erosion.